2003
DOI: 10.1113/jphysiol.2002.033746
|View full text |Cite
|
Sign up to set email alerts
|

Action Potentials in Basal and Oblique Dendrites of Rat Neocortical Pyramidal Neurons

Abstract: Basal and oblique dendrites comprise ~2/3 of the total excitable membrane in the mammalian cerebral cortex, yet they have never been probed with glass electrodes, and therefore their electrical properties and overall impact on synaptic processing are unknown. In the present study, fast multisite voltage-sensitive dye imaging combined with somatic recording was used to provide a detailed description of the membrane potential transients in basal and oblique dendrites of pyramidal neurons during single and trains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
137
9
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(159 citation statements)
references
References 49 publications
11
137
9
2
Order By: Relevance
“…1 B), according to previous work modeling this cell (Rhodes and Gray, 1994;Rhodes, 1999;Rhodes and Llinás, 2001), in which details of current kinetics may be found. The distribution of dendritic ionic conductances included Na ϩ conductance density (12 mS/cm 2 ) in the basal dendrites consistent with the measurements of Antic (2003), along with high-threshold Ca 2ϩ densities of 6 -12 mS/cm 2 , adequate to drive the bursts characteristic of this cell type (McCormick et al, 1985;Rhodes and Gray, 1994). The distribution of ionic conductance densities specified in Table 1 was used for all that were simulated, unless specifically noted otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…1 B), according to previous work modeling this cell (Rhodes and Gray, 1994;Rhodes, 1999;Rhodes and Llinás, 2001), in which details of current kinetics may be found. The distribution of dendritic ionic conductances included Na ϩ conductance density (12 mS/cm 2 ) in the basal dendrites consistent with the measurements of Antic (2003), along with high-threshold Ca 2ϩ densities of 6 -12 mS/cm 2 , adequate to drive the bursts characteristic of this cell type (McCormick et al, 1985;Rhodes and Gray, 1994). The distribution of ionic conductance densities specified in Table 1 was used for all that were simulated, unless specifically noted otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…Backpropagating APs have the advantage of being generated in the soma. They start with impressive amplitudes (~ 100 mV), and even in the absence of dendritic sodium conductance they can backpropagate passively and cause substantial voltage transients in basal dendrites, as revealed in the detailed multicompartmental models of the pyramidal layer V neuron (Rapp et al, 1996;Vetter, Roth & Hausser, 2001;Antic, 2003). Locally triggered basal spikelets on the other hand, not only lack the passive boost of the somatic AP, but even worse, their generator current is sucked up by an enormous nearby current sink -the cell body.…”
Section: The Incidence Of Basal Spikeletsmentioning
confidence: 99%
“…Basal spikelets could perhaps be just a side product of sodium channel proteins that were originally placed there to support action potential backpropagation in thin dendrites (Antic, 2003). These and other hypotheses concerning the functional significance of basal spikes, and their potential role in cortical signal processing, are currently under active investigation.…”
mentioning
confidence: 99%
“…Using this method to compare the first and third action potential signal in a burst, a recent study concluded that action potentials are significantly attenuated as they propagate into distal The increasing delay between the signal from the somatic region and proximal dendritic segments reflects the time taken for the propagation of the action potential to dendritic locations. Taken from [2] basal dendrites of pyramidal neurons [26], in contrast to the conclusions of Antic [5].…”
Section: Voltage Imaging Using Internally Applied Dyesmentioning
confidence: 96%
“…2) [2]. A follow-up study examined action potential back-propagation into basal dendrites in cortical pyramidal neurons in more detail [5], concluding that action potentials backpropagate up to 200 μm from the soma with little amplitude and shape modulation.…”
Section: Voltage Imaging Using Internally Applied Dyesmentioning
confidence: 99%